Effect of axial loads on implanted-supported partial fixed prostheses by strain gauge analysis - Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Nishioka, Renato Sussumu [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Braulino de Melo Nishioka, Lea Nogueira (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objectives: The present study used strain gauge analysis to perform an in vitro evaluation of the effect of axial loading on 3 elements of implant-supported partial fixed prostheses, varying the type of prosthetic cylinder and the loading points. Material and methods: Three internal hexagon implants were linearly embedded in a polyurethane block. Microunit abutments were connected to the implants applying a torque of 20 Ncm, and prefabricated Co-Cr cylinders and plastic prosthetic cylinders were screwed onto the abutments, which received standard patterns cast in Co-Cr alloy (n=5). Four strain gauges (SG) were bonded onto the surface of the block tangentially to the implants, SG 01 mesially to implant 1, SG 02 and SG 03 mesially and distally to implant 2, respectively, and SG 04 distally to implant 3. Each metallic structure was screwed onto the abutments with a 10 Ncm torque and an axial load of 30 kg was applied at five predetermined points (A, B, C, D, E). The data obtained from the strain gauge analyses were analyzed statistically by RM ANOVA and Tukey's test, with a level of significance of p<0.05. Results: There was a significant difference for the loading point (p=0.0001), with point B generating the smallest microdeformation (239.49 mu epsilon) and point D the highest (442.77 mu epsilon). No significant difference was found for the cylinder type (p=0.748). Conclusions: It was concluded that the type of cylinder did not affect in the magnitude of microdeformation, but the axial loading location influenced this magnitude.
Keywords: Biomechanics; Dental implants; Dental prosthesis; Implant-supported dental prosthesis